ChemInform Abstract: Highly Efficient Direct Allylation of Oxindoles with Simple Allylic Alcohols Enabled by Palladium/Broensted Acid Catalysis. Issue 10 (March 2015) - Yang, Huameng; Zhou, Hui; Yin, Hongyu; Xia, Chungu; Jiang, Gaoxi
Abstract Preliminary experiments towards an asymmetric allylation of (Ia) with (II) using chiral mono or diphosphine ligands furnish (IIIa) with up to 17% enantiomeric excess only.